Designing interactive augmented reality application for student's directed learning of continuous distillation process - Gao, Sitian (2023)
Continuous distillation is an important separation process in chemical engineering curriculum. Conventionally, it is often taught as black box diagrams that lack user visibility, thus preventing students from developing a deeper understanding and comprehension. This paper presents the technical development of the mobile AR application and its implementation in the curriculum of Chemical Engineering Unit Operations at Nanyang Technological University Singapore. The mobile AR application is to provide interactive visualization and real-time numerical simulation to promote students’ active learning in the classroom. The results of the pre-test and post-test indicated that the AR application helped students gain a better understanding of the principle and fundamental concepts of the distillation process. The evaluation survey with 6-point likert scale questions shows that students had a positive experience using the mobile AR application and it has enhanced their learning experience, as suggested by a mean evaluation score of 5.18 out of 6.0.